THE DERIVATIVE ACTION: THE PROBLEMS OF LAW ENFORCEMENT - Васильева, Татьяна Андреевна Андреевна (Teisė, 2017)
The article is devoted to analysis of the problems of application of the derivative action in court practice. Special attention is paid to computation of period of limitation, definition interested person, procedural position of member and legal persons in procedure on the derivative action, court costs, evidence of bad faith and unreasonableness of Director‘s actions and others.